Ferroptosis: roles and molecular mechanisms in diabetic cardiomyopathy - Zhao, Yangting; Pan, Binjing; Lv, Xiaoyu; Chen, Chongyang; Li, Kai; Wang, Yawen; Liu, Jingfang (Frontiers in Endocrinology, 2023)
Diabetic cardiomyopathy (DCM) is a serious complication of type 1 and type 2 diabetes, which leads to the aggravation of myocardial fibrosis, disorders involving systolic and diastolic functions, and increased mortality of patients with diabetes through mechanisms such as glycolipid toxicity, inflammatory response, and oxidative stress. Ferroptosis is a form of iron-dependent regulatory cell death that is attributed to the accumulation of lipid peroxides and an imbalance in redox regulation. Increased production of lipid reactive oxygen species (ROS) during ferroptosis promotes oxidative stress and damages myocardial cells, leading to myocardial systolic and diastolic dysfunction. Overproduction of ROS is an important bridge between ferroptosis and DCM, and ferroptosis inhibitors may provide new targets for the treatment of patients with DCM.